State Vocational High School: Educational Investment for the Future in the Mandalika Special Economic Zone - West Nusa Tenggara - Fathurrahman; Samlan; Abdul Haris Khoirul Alam (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This article examines the urgency of establishing a State Vocational Madrasah Aliyah (MAKN) in the Mandalika Special Economic Zone (KEK), West Nusa Tenggara, as a strategic investment in meeting the needs of education and skilled labor in the tourism sector and related industries. The Mandalika KEK, as a super-priority tourism destination, requires competent human resources to support economic growth while still fortifying the "moral-religious" spirit of the local community from the onslaught of various tourist cultures that come one after another. This article uses a qualitative method with a literature study approach, secondary data analysis, and interviews with relevant stakeholders, including local government officials, tourism industry players, and community leaders. The results of the analysis show that the establishment of MAKN with relevant vocational programs, such as hospitality, culinary arts, and tourism, will have a significant positive impact. MAKN is expected to improve the quality of local human resources, create jobs, and encourage the development of small and medium enterprises. In addition, MAKN is also likely to support sustainable development in the area. Support from the local government, the Ministry of Religion, and industry players is a crucial factor in realizing a quality and competitive MAKN. This article concludes that the establishment of MAKN is an important educational investment for the future of Mandalika, in line with the National Long-Term Development Plan (RPJPN) 2025-2045, and recommends a policy of important collaboration between various parties to ensure the success of its implementation.